Teacher Written Feedback In Efl Yemeni Context: A Qualitative Case Study Of Students’ Reactions And Utilisations - Mahfoodh, Omer Hassan Ali (2011)

(untitled)
Teacher written feedback is the input from a reader to a writer with the effect of providing information to the writer for revision. This qualitative case study attempted to investigate eight English major EFL Yemeni students’ reactions to and utilisations of their teachers’ written feedback. The study is built on the most dominant theories in learning, writing, and revision. These theories are the cognitive process theory of writing, the socio-cultural theory of learning, the social constructivism theory of learning, and the revision process theory.